2014
DOI: 10.1097/acm.0000000000000143
|View full text |Cite
|
Sign up to set email alerts
|

The Nursing Home as a Learning Environment

Abstract: To the authors' knowledge, this study is one of the first to identify characteristics of the nursing home as a learning environment. The main challenge in the nursing home is dealing with less, which, according to the residents in the present study, often leads to learning more. To ensure that learning really happens, the authors call for high-quality supervision to support learners in the nursing home environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This emphasises the importance of giving aged care staff, particularly those engaged in mentoring nursing students, the opportunity to meet and critically reflect on the challenges and opportunities within this educational framework. This supports evidence from international studies, which indicates that Teaching Nursing Homes provide effective nurse training in the context of a collaborative, inter-disciplinary learning environment, where students can experience and contribute to team-based care [ 6 , 7 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This emphasises the importance of giving aged care staff, particularly those engaged in mentoring nursing students, the opportunity to meet and critically reflect on the challenges and opportunities within this educational framework. This supports evidence from international studies, which indicates that Teaching Nursing Homes provide effective nurse training in the context of a collaborative, inter-disciplinary learning environment, where students can experience and contribute to team-based care [ 6 , 7 ].…”
Section: Discussionsupporting
confidence: 76%
“…To redress a widening gap between workforce quality and demand for care, the Wicking Dementia Research and Education Centre (University of Tasmania) has instituted a program to develop a network of Teaching Aged Care Facilities (TACF). This program draws on evidence from the development of Teaching Nursing Homes in the United States of America and Scandinavia, which have been shown to provide effective healthcare student training when they deliver a collaborative, inter-disciplinary learning environment where students can experience team-based care and opportunities for independent assessment [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown how nursing homes can offer medical students and newly qualified doctors a broad range of specific geriatric and long term care learning outcomes [ 12 , 29 , 30 ]. In this study we focused on EOL care and dialogues about death, emphasizing the impact of situated learning on development of doctors’ professional role.…”
Section: Discussionmentioning
confidence: 99%
“…Residential aged care facilities (RACF) have been identified as non-traditional environments in which to conduct clinical placements for health professional education (Molema, et al, 2014), particularly for many allied health disciplines (Liebig, 2008, Mezey, et al, 2008. The RACF is not a commonly sought after placement opportunity by students due to the perceived unattractive and sometimes confronting nature of ageing (Stevens, 2011).…”
Section: Introductionmentioning
confidence: 99%